A distinct geological collection: the Litoteca IGc/USP and its museological processes - Lima, Jéssica Tarine Moitinho de; Sborja, Camila Hoshino (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Science and technology collections are intrinsic to their kind of knowledge produced by society in all areas of knowledge. They are interlinked to the professionals’ memory and practices in spaces of production, scientific dynamics, technological development and teaching. Geological collections, as part of the science and technology collections, are witness of the scientific process, mostly originating in an academic environment. This heritage is commonly found within Brazilian universities, being analysed here through the case study of the practices of the Litoteca IGc/USP, a laboratory belonging to the Museu de Geociências (Geosciences Museum), Instituto de Geociências, Universidade de São Paulo (Geosciences Institute at the University of São Paulo – IGc/USP). The life cycle of this heritage is intrinsic to various curation and management actions involving everything from the decision-making process to the most common actions of backing, identifying and processing information. The aim of this article is to demonstrate the process of the lithological property incorporated into an ex-situ collection, valued and then recognized as a museum document. The result of this processing is connected to scientific communication activities that attest to the property’s belonging to a collection, reinforcing its links and social function.
Keywords: Documentation; Scientific communication; Geological heritage; Museology